POETIC NARRATIVES OF A PAINTING ATELIER AND ITS TRAINING CONTRIBUTION (Palíndromo, 2019)
The present text is an analysis of the development and application of a curriculum of Visual Arts, as well as the creation of the 1336 painting studio that compose it and, ultimately, the development of the painting research of the three authors of the text located in this space. The purpose of the writing is to analyze the construction of this curriculum at the Universidade Federal de Santa Maria and its implications on the formative structure of 1336 painting studio. It seeks to investigate how space images produced poetic narratives and how its objects could affect the artistic production of the three authors of the text. Thus, the research describes that each one of the authors developed differently, but in the same space of meeting and sharing. As methodological subsidies used were: interview and documentary / bibliographic research. In this way, it is understood that the research on the formation of an individual and collective narrative shows how the images can be creation propulsion and formative contribution.
Keywords: poetical narratives; curriculum; 1336 painting studio